Persistent Mayer Dirac - Faisal Suwayyid; Guo-Wei Wei (Journal of Physics: Complexity)
Topological data analysis (TDA) has made significant progress in developing a new class of fundamental operators known as the Dirac operator, particularly in topological signals and molecular representations. However, the current approaches being used are based on the classical case of chain complexes. The present study establishes Mayer Dirac operators based on N -chain complexes. These operators interconnect an alternating sequence of Mayer Laplacian operators, providing a generalization of the classical result $D^2 = L$ . Furthermore, the research presents an explicit formulation of the Laplacian for N -chain complexes induced by vertex sequences on a finite set. Weighted versions of Mayer Laplacian and Dirac operators are introduced to expand the scope and improve applicability, showcasing their effectiveness in capturing physical attributes in various practical scenarios. The study presents a generalized version for factorizing Laplacian operators as an operator’s product and its ‘adjoint’. Additionally, the proposed persistent Mayer Dirac operators and extensions are applied to biological and chemical domains, particularly in the analysis of molecular structures. The study also highlights the potential applications of persistent Mayer Dirac operators in data science.